Mass spectrometry-based multimodal approaches for the identification and quantification analysis of microplastics in food matrix - Wu, Pengfei; Wu, Xiaoyi; Huang, Qing; Yu, Qinwei; Jin, Hangbiao; Zhu, Minghai (Frontiers in Nutrition, 2023)
Background: Microplastics (MPs) and nanoplastics (NPs) have become emerging contaminants worldwide in food matrices. However, analytical approaches for their determination have yet to be standardized. Therefore, a systematic study is urgently needed to highlight the merits of mass spectrometry (MS) based methods for this applications. Purpose: The aim of the study is to review the current status of MS as applied to multimodal analysis of MPs in food matrices. Methods: Web of Science and Google Scholar databases were searched and screened until Jan. 2023. Inclusion criteria: “publication years” was set to the last decades, “English” was selected as the “language”, and “research area” was set to environmental chemistry, food analysis and polymer science. The keywords were “microplastics”, “nanoplastics”, “determination”, “identification/quantification” and “mass spectrometry”. Results: Traditional spectrometry techniques offer good abilities to conduct the multimodal analysis of MPs in terms of the color, shape and other morphologies. However, such technologies have some limitations, in particular the relatively high limits of detection. In contrast, MS-based methods supply excellent supplements. In MS-based methods, GC-MS and LC-MS/MS were selected as representative methods for determining MPs in the food matrices, while specialized MS methods (i.e., MALDI-ToF MS and ToF-SIMS) were considered to offer great potential in multimodal analysis of MPs especially when interfaced with imaging system. Significance: This study will contribute to gaining a deeper insight into the assessment of the exposure levels of MPs in human body, and may help build a bridge between the monitoring studies and the toxicology field.